Weight-lifting Injuries: A Review of Imaging and Biomechanics - Igbinoba, Zenas; Miller, Theodore T. (Seminars in Musculoskeletal Radiology, 2025)
Weight lifting, although offering substantial health benefits such as improved bone density, muscle strength, and cardiovascular fitness, poses significant injury risks. In this article, we review common weight-lifting injuries associated with specific activities of Olympic lifts, bench press, deadlift, and squat, as well as general weight-lifting injuries.
Keywords: weight lifting; sports injuries; Olympic lifts; biomechanics